Anthropology and ethnography are not equivalent : reorienting anthropology for the future - Ahmad, Irfan, 1974- (Methodology and history in anthropology, 2021)
"In recent years, crucial questions have been raised about anthropology as a discipline, such as whether ethnography is central to the subject, and how imagination, reality and truth are joined in anthropological enterprises. These interventions have impacted anthropologists and scholars at large. This volume contributes to the debate about the interrelationships between ethnography and anthropology and takes it to a new plane. Six anthropologists with field experience in Egypt, Greece, India, Laos, Mauritius, Thailand and Switzerland critically discuss these propositions in order to renew anthropology for the future. The volume concludes with an Afterword from Tim Ingold"--